2004
DOI: 10.1177/0748730403260776
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Precision in the Mammalian Circadian System: A Reliable Clock from Less Reliable Neurons

Abstract: The mammalian SCN contains a biological clock that drives remarkably precise circadian rhythms in vivo and in vitro. This study asks whether the cycle-to-cycle variability of behavioral rhythms in mice can be attributed to precision of individual circadian pacemakers within the SCN or their interactions. The authors measured the standard deviation of the cycle-to-cycle period from 7-day recordings of running wheel activity, Period1 gene expression in cultured SCN explants, and firing rate patterns of dispersed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
239
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(252 citation statements)
references
References 53 publications
11
239
1
1
Order By: Relevance
“…In particular, the number of cells and the proportions of different cell types affect period and the stability of rhythms [8,19,12,18]. If functionally different cells are produced at different times, as the present results indicate [4], then small changes in the duration or intensity of proliferation of SCN progenitors at different times in development could be one source of variation (both within and between species) in the overall function of the nucleus.…”
Section: Discussionmentioning
confidence: 56%
“…In particular, the number of cells and the proportions of different cell types affect period and the stability of rhythms [8,19,12,18]. If functionally different cells are produced at different times, as the present results indicate [4], then small changes in the duration or intensity of proliferation of SCN progenitors at different times in development could be one source of variation (both within and between species) in the overall function of the nucleus.…”
Section: Discussionmentioning
confidence: 56%
“…It is a network of multiple autonomous noisy oscillators, which communicate via neuropeptides to synchronize and form a coherent oscillator (Herzog et al 2004;Liu et al 2007). This coherent oscillator then coordinates the timing of daily behaviours, such as the sleep/wake cycle.…”
Section: Modelling Coupled Stochastic Mammalian Neuronsmentioning
confidence: 99%
“…Although in Welsh et al's preparation a substantial number of neural connections remained, in a tissue explant from the SCN even more are retained. Herzog, Aton, Numano, Sakaki, and Tei (2004) showed that over a seven--day interval the SD of Per1 expression in explants was much less than the SD for the firing rate of dispersed neurons and closely approximated that of the running wheel behavior in the intact mouse. As shown in panels A and B of Figure 6, using a luciferase knock--in under the Per2 gene in SCN slices dispersed SCN neurons, Liu, Welsh, Ko, Tran, Zhang, Priest, Buhr, Singer, Meeker, Verma, Doyle, Takahashi, and Kay (2007) provided a compelling demonstration of the contrast in synchronization obtained between a SCN slice and dispersed neurons.…”
Section: Integrating Intracellular Operations Into An Intercellular Nmentioning
confidence: 87%